Treatment of opioid use disorder, opioid withdrawal symptoms and chronic pain - BRIONES MARISA S; HEINZERLING KEITH G; DEYOUNG DUSTIN Z (2020)
The current methods and compositions provide for a novel and effective therapeutic method for treating opioid use disorder, opioid withdrawal symptoms and/or chronic pain. Accordingly, certain aspectsof the disclosure relate to a method for treating opioid use disorder, opioid withdrawal symptoms and/or chronic pain in a subject, and the method comprises administering at least one purified cannabinoid compound and a partial opioid agonist. In some embodiments, the method comprises administering a composition comprising cannabidiol and buprenorphine. 本发明的方法和组合物提供了用于治疗阿片样物质使用障碍、阿片样物质戒断症状和/或慢性疼痛的新且有效的治疗方法。因此，本公开内容的某些方面涉及用于在对象中治疗阿片样物质使用障碍、阿片样物质戒断症状和/或慢性疼痛的方法，所述方法包括施用至少一种经纯化的大麻素化合物和阿片样物质部分激动剂。在一些实施方案中，所述方法包括施用包含大麻二酚和丁丙诺啡的组合物。